Pharmacological Characterization of ZYAN1, a Novel Prolyl Hydroxylase Inhibitor for the Treatment of Anemia - Jain, M. R.; Joharapurkar, A. A.; Pandya, V.; Patel, V.; Joshi, J.; Kshirsagar, S.; Patel, K.; Patel, P. R.; Desai, R. C. (Drug Research, 2016)
Prolyl hydroxylase (PHD) inhibitors stabilize hypoxia inducible factor (HIF), and exert antianemic effect by potentiating erythropoietin (EPO) expression and down-regulation of hepcidin. ZYAN1 is a novel PHD inhibitor under clinical development for the treatment of anemia. The pharmacodynamic effects of acute and chronic dosing of ZYAN1 were assessed in normal and 5/6 nephrectomized Wistar rats. The effect of ZYAN1 was also investigated in cisplatin-induced anemia using C57 mice. Acute treatment with ZYAN1 increased circulating EPO levels (10.3±3.7 and 40.0±8.5 fold rise at 15 and 30 mg/kg, respectively), reticulocyte count (4.2±0.5 and 6.0±0.2 fold rise at 15 and 30 mg/kg, respectively) and stabilized HIF (28% increase at 45 mg/kg) in normal rats. Nephrectomized rats showed similar dose-related pharmacodynamic effects. In a 28-day study in nephrectomized rats, ZYAN1 administered every alternate day, caused increase in hemoglobin (1.9±0.3 and 2.5±0.4 g/dL) and RBC count (10.7±4.0 and 14.0±4.1%) at 15 and 30 mg/kg respectively. In cisplatin-treated mice also an increase in hemoglobin (3.4±0.2 and 5.9±0.2 g/dL) and RBC count (22.5±2.2 and 37.3±1.7%) at 15 and 30 mg/kg respectively was observed. ZYAN1’s effects on hemoglobin and RBC count were distinct from darbepoietin. ZYAN1 demonstrated hematinic potential by combined effects on EPO release and efficient iron utilization. The efficacy of ZYAN1 in disease models of different etiologies suggests that it will be useful in treating wide spectrum of anemia patients.
Keywords: novel drug; HIF; hepcidin; CKD; chemotherapy